2022
DOI: 10.1177/19476035221085146
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Large Cartilage Defects in the Knee by Hydrogel-Based Autologous Chondrocyte Implantation: Two-Year Results of a Prospective, Multicenter, Single-Arm Phase III Trial

Abstract: Objective To evaluate the clinical outcome of a hydrogel-based autologous chondrocyte implantation (ACI) for large articular cartilage defects in the knee joint. Design Prospective, multicenter, single-arm, phase III clinical trial. ACI was performed in 100 patients with focal full-thickness cartilage defects ranging from 4 to 12 cm2 in size. The primary outcome measure was the responder rate at 2 years using the Knee Injury and Osteoarthritis Outcome Score (KOOS). Results Two years after ACI treatment, 93% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…In our study, the analysis showed a significant decrease in mean T 2 between 12 and 24 months only in repair cartilage (Δ = 5.82 ± 6.48, p < 0.001). Decreased T 2 values in combination with a high morphological score (MOCART) indicated a favorable clinical outcome, which is in correspondence with the clinical results of this study published by Niemeyer et al [27]. A decrease in the mean T 2 value of a selected ROI is very general and represents only one mean quantitative value for the whole area without providing information about changes in cartilage texture; therefore, texture analysis might be a useful add-on.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the analysis showed a significant decrease in mean T 2 between 12 and 24 months only in repair cartilage (Δ = 5.82 ± 6.48, p < 0.001). Decreased T 2 values in combination with a high morphological score (MOCART) indicated a favorable clinical outcome, which is in correspondence with the clinical results of this study published by Niemeyer et al [27]. A decrease in the mean T 2 value of a selected ROI is very general and represents only one mean quantitative value for the whole area without providing information about changes in cartilage texture; therefore, texture analysis might be a useful add-on.…”
Section: Discussionsupporting
confidence: 90%
“…Five patients from the MRI cohort were excluded, due to a small defect size, resulting in 20 evaluable patients (with overall 23 lesions). Detailed information about postoperative recovery and rehabilitation of all patients can be found in Niemeyer et al [27].…”
Section: Study Design and Patient Baseline Characteristicsmentioning
confidence: 99%
“…42 A recent prospective clinical trial reported high MOCART (Magnetic Resonance Observation of Cartilage Repair Tissue) score up to 80 points for hyaluronic acid-based ACI as used in this study in comparison with previously reported ACI products indicating superior regenerative tissue. 43 Therefore, the reported clinical results may reflect a superior chrondrogenic graft maturation as seen in our laboratory study.…”
Section: Discussionmentioning
confidence: 50%
“…48 Clinically, no delamination has been reported for the HA. 43 In addition, strong graft incorpotation may allow early weightbearing, which is crucial to allow for mechano-induced chondrocyte differentiation. 23 Mechanotransduction is an important mechanism of graft maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the current strategy is to use tissue-engineered scaffolds to maintain the differentiated state of chondrocytes and impel cells to chondrogenesis (Liu et al, 2019). In a prospective multicenter phase III clinical study, hydrogels with autologous chondrocytes were implanted to treat knee articular cartilage defects, and over a 2-year followup, repair tissues matured, recombined, and integrated with surrounding tissues, demonstrating that hydrogel-based ACI was a valuable measure for the treatment of knee cartilage defects in patients (Niemeyer et al, 2022). Other exogenous MSCs could also play a similar role in the treatment of cartilage defects as autologous chondrocytes.…”
Section: Cellmentioning
confidence: 99%